Design of Recommendation Decision Support System ITERA Industrial Engineering Students' Final Project Topic with Method Case-Based Reasoning and Certainty Factors - Yanuarso, Hersa Dwi; Kusuma, David; Muttaqin, Muhammad Faishal Jundana; Hadi, M. Zaky; Didin, Fatin Saffanah (JUMANTARA: Jurnal Manajemen dan Teknologi Rekayasa, 2026)
Design of Decision Support System (DSS) for final project topic recommendation for ITERA Industrial Engineering students by integrating Case-Based Reasoning (CBR) and Certainty Factor (CF) methods used to support this research. A common problem is when determining the final project research topic, where most students have difficulty finding a topic that is in accordance with their respective fields of expertise. This causes the final project to take longer than the estimated standard time for graduates, which is normally between 4-5 years. The purpose of this study is to assist final year students in determining the final project title that suits their preferences and academic needs. The CBR method is used to search and compare cases based on case similarities with data contained in the database, while the CF value is applied to handle uncertainty and provide a level of confidence in the resulting recommendations. The results show that the integration of these two methods improves the accuracy and relevance of recommendations, as well as providing better transparency through the presentation of Certainty Factor values. System evaluation shows a high level of user satisfaction and a decrease in the time required to determine the final project topic. The design and development of a decision support system for final project topic recommendations was successfully carried out by integrating the Case-based Reasoning and Certainty Factor methods implemented on web hosting, performance evaluation and the impact of system use on user satisfaction showed that users felt satisfied when using the decision support system.